L-Proline-Catalyzed Synthesis of Phthalimide Derivatives and Evaluation of Their Antioxidant, Anti-Inflammatory, and Lipoxygenase Inhibition Activities - Shagufta Perveen; Raha Orfali (Journal of Chemistry)
A study was planned to synthesize the phthalimide derivatives as phthalimides have versatile biological activities. To synthesize the phthalimide derivatives, initially the reaction was optimized with various catalysts, and L-proline was found to be the best catalyst as it provided excellent yield. A series of phthalimide derivatives was synthesized by facile one-top reaction of phthalic acid with aryl amines under mild reaction conditions in the presence of L-proline as catalyst. Products were obtained in excellent yields and structurally characterized by 1H, 13C NMR, and mass spectral data. Products 1–7 were evaluated for antioxidant, anti-inflammatory, and lipoxygenase enzyme inhibition activities. Compounds 1 and 4 showed potent antioxidant activity under DPPH with IC50 values 27.3 and 25.0 μM when compared with the standard BHA (IC50 = 44.2 μM), respectively. Compounds 1 and 4 further showed strong lipoxygenase inhibition activity with IC50 values 21.34 and 20.45 μM when compared with standard baicalein (IC50 = 22.60 μM), respectively. Compound 2 was found to be promising and about equal to the used standard aspirin in the inhibition of bovine serum albumin denaturation, while other compounds showed weak-to-moderate % inhibition.